Fiber bragg grating sensors for pH and humidity measurement - Yulianti, Ian (2013)
pH sensor and humidity sensor have received much attention since their application is of great importance in many fields. Due to their advantages, optical fiber sensors have been introduced and investigated to overcome the limitation of conventional pH and humidity sensors. However, there are some drawbacks, such as low sensitivity, low accuracy and low multiplexing capability of the current optical sensors. This thesis presents the design and development of new optical fiber sensors for pH and humidity measurement by adopting fiber Bragg grating (FBG) technique. Three types of sensor design which are hydrogel coated-unetched FBGs, hydrogel coated-etched FBGs and elastomer-hydrogel coated FBGs are proposed for pH measurement. FBG based-Fabry-perot (FBG-FP) was proposed as humidity sensor with temperature compensation. The coating thickness on the cavity is higher than that on the FBGs to obtain different humidity response and temperature response. The working principle of both FBG pH sensors and humidity sensors relies on stress induced on the fiber due to mechanical expansion of swelling sensing materials coated on the FBG. The swelling sensing material used to construct FBG pH sensors is pH sensitive hydrogel synthesised by Hydroxyethyl Methacrylate (HEMA), acrylic acid and ethylene glycol dimethacrylate as crosslinker. Meanwhile, the swelling sensing material used to construct FBG humidity sensors is polyimide. Optimisation of the FBG pH sensors was done by analysing the strain induced in the FBG due to swelling of the coating material. The swelling of pH sensitive hydrogel was modeled using free energy function and was solved using finite element method by adopting ABAQUS software. Theoretical analysis of the FBG-FP response to humidity and temperature change was done using coupled mode theory. For FBG-FP humidity sensor, calculation results show that the humidity sensitivity and thermal sensitivity are 1.92pm/%RH and 8.87pm/ oC, respectively, for polyimide coating thickness of 10µm on the FBG and 15µm on the cavity. Fabrications were done for both pH sensor and humidity sensor. For pH sensor, hydrogel coated-etched FBG with hydrogel coating thickness of 90µm and etched fiber diameter of 40µm was fabricated and characterised. Results indicate that the sensor has a good reversibility and provides linear response in pH range of 4.97 to 7.17 with sensitivity of 0.056nm/pH unit and 0.195nm/pH unit at pH of 4.97 and 7.17, respectively. For FBG-FP humidity sensor with recoated diameter of 145µm on the FBG and 157µm on the cavity, the experimental results show that the humidity sensitivity and thermal sensitivity are 1.75×10-3nm/%RH and 1.52×10-2nm/oC, respectively.